Pemahaman Ketaatan Kepada Pemimpin Menurut Ibrani 13:17 - Sjanette Eveline (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2021)
Obedience or obedience is an attitude that is subject to authority, carrying out what is ordered, obeying what is demanded or keeping away from what is prohibited. Obedience issues are related to regulations. Humans prefer disobedience, if there are rules to obey, so violations occur here. This has happened since in the Garden of Eden. And it continues to grow in various aspects of life to date. Obedience is a decision to serve the obedient leader. Service and obedience are two things that are side by side like Siamese twins. Through expressions that contain teaching that is so strict, that if someone likes to serve or feels called in a certain field of service, but has a rebellious heart to the leader, it is showing a failure to understand the meaning of a service. Obedience of the servants is clearly very instrumental in solving the problem that is happening. Abstrak Indonesia Taat atau ketaatan adalah sikap yang tunduk kepada wewenang, menjalankan apa yang diperintahkan, mematuhi apa yang dituntut atau menjauhkan diri dari apa yang dilarang. Persoalan ketaatan terkait dengan peraturan. Manusia lebih suka tidak taat, jikalau ada aturan supaya taat, sehingga terjadilah pelanggaran di sini. Ini telah terjadi sejak di Taman Eden. Dan terus berkembang dalam aneka segi kehidupan sampai saat ini. Ketaatan itu merupakan keputusan untuk mau melayani pemimpin yang ditaati tersebut. Pelayanan dan ketaatan adalah dua hal yang berdampingan seumpama kembar siam. Melalui ungkapan yang mengandung pengajaran yang begitu ketat, bahwa jikalau seseorang suka melayani atau merasa terpanggil dalam bidang pelayanan tertentu, namun memiliki hati yang suka berontak kepada sang pemimpinnya, itu sedang menunjukkan adanya kegagalan dalam memahami arti sebuah pelayanan. Ketaatan para pelayan ini jelas sangat berperan dalam penyelesaian masalah yang sedang terjadi.